Level of Awareness on Covid-19 Vaccine Administration among Health Care Professionals as Determinants to Safe Vaccine Administration in the Integrated Provincial Health Office and City Health Office Marawi City, Philippines (London Journal of Medical and Health Research, 2023)
Vaccines have played an important role in the lives of the people, most especially the children. It has helped prevent and protect the spread of contagious, dangerous and deadly diseases. Getting vaccinated produces antibodies that will fight that antigens in someone’s body. Thus, it keeps an individual from getting and spreading the disease. In other words, a vaccine is a safer substitute for an individual’s first exposure to a disease. The individual gets protection without having to get sick. Through vaccination, people can develop immunity without suffering from the actual diseases that vaccines prevent.